Analisis Komparasi Kinerja Keuangan Bank Syariah dengan Bank Non Syariah di Indonesia - Yogi Kurniawan; Mufti Arief Arfiansyah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
The development of Indonesia's financial system has shown rapid growth, with Islamic banks increasingly occupying a significant position in providing financial services in accordance with Islamic principles. However, views on the financial performance of Islamic and conventional banks in Indonesia still vary. Therefore, this research aims to examine the differences in financial performance between Islamic and conventional commercial banks during the period of 2018-2022. In this study, the purposive sampling method was used to select samples from eleven conventional and Islamic commercial banks. Secondary data in the form of financial reports were obtained from the official website of the Financial Services Authority (OJK) and the official websites of the banks under study. The tested research variables include Risk Profile ratios, Good Corporate Governance (GCG), Earnings, and Capital. Hypothesis testing was conducted by applying independent sample t-tests and Mann-Whitney tests for data analysis. The findings indicate that there is no significant difference in credit risk and liquidity risk between the two categories of banking institutions. However, there is a significant difference in the implementation of GCG and Return on Assets (ROA) between Islamic and conventional commercial banks. Overall, the financial performance of Islamic Commercial Banks demonstrates superiority in ROA and Capital Adequacy Ratio (CAR), while Conventional Commercial Banks excel in Good Corporate Governance (GCG) and Operational Cost to Operating Income (BOPO).